Investigations in European antitrust law - Dannecker, Gerhard (European Integration Studies, 2023)
The Commission is responsible for investigating cartel law violations and imposing fines on companies. The investigations are carried out in an administrative procedure in which the facts of the case must be investigated in compliance with the rule of law. Here, fundamental rights must be guaranteed. In this respect, the jurisdiction of the ECJ still shows deficits, as it is based on the assumption that human rights belong exclusively to human beings. When legal persons are fined, they must be granted the guarantees of constitutional law.